2020
DOI: 10.1108/ijwbr-05-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Tequila at home or abroad? paths to brand love and purchase loyalty for hedonic products

Abstract: Purpose This study aims to examine the impact of consumer brand experience on brand love and loyalty toward a favorite tequila brand across Mexico and the USA while advancing marketing strategies to strengthen consumer-brand relationships. Design/methodology/approach Data were analyzed from 906 respondents (348-USA and 558-Mexico) to assess paths to purchase loyalty and test brand relationship hypotheses using partial least squares. Findings Analysis revealed that consumers in both markets demonstrated sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The concept of brand love has been studied for over a decade in various industry contexts, including fashion (Bairrada et al, 2019; Junaid et al, 2019), technologies (Bergkvist & Bech‐Larsen, 2010; Rodrigues & Rodrigues, 2019), automobiles (Albert & Merunka, 2013; Bergkvist & Bech‐Larsen, 2010; Delgado‐Ballester et al, 2017; Islam & Rahman, 2016; Junaid et al, 2019; Palazón et al, 2019), tourism (Alnawas & Altarifi, 2016; Aro et al, 2018; Bigne et al, 2020; Rodrigues et al, 2021), wine (Cacho‐Elizondo et al, 2020) and sports (Karjaluoto et al, 2016; Zhou et al, 2020), as well as counterfeit luxury goods (Chand & Fei, 2021). This wide range supports Fetscherin et al (2014) observation that brand love is not industry specific.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The concept of brand love has been studied for over a decade in various industry contexts, including fashion (Bairrada et al, 2019; Junaid et al, 2019), technologies (Bergkvist & Bech‐Larsen, 2010; Rodrigues & Rodrigues, 2019), automobiles (Albert & Merunka, 2013; Bergkvist & Bech‐Larsen, 2010; Delgado‐Ballester et al, 2017; Islam & Rahman, 2016; Junaid et al, 2019; Palazón et al, 2019), tourism (Alnawas & Altarifi, 2016; Aro et al, 2018; Bigne et al, 2020; Rodrigues et al, 2021), wine (Cacho‐Elizondo et al, 2020) and sports (Karjaluoto et al, 2016; Zhou et al, 2020), as well as counterfeit luxury goods (Chand & Fei, 2021). This wide range supports Fetscherin et al (2014) observation that brand love is not industry specific.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Relationship between Brand Love and Brand Loyalty. Brand love can form customer loyalty, which encourages consistent repeat purchases to only one brand (Cacho-Elizondo et al, 2021). Customers will further increase loyalty if they feel a positive emotional attachment to a brand (Le, 2021).…”
Section: Relationship Between Brand Identification Social Media Marke...mentioning
confidence: 99%
“…Francioni et al (2022) identified country-of-origin and word-of-mouth as influencing factors for developing BL for beers. Cacho-Elizondo et al (2021) investigated the relationship between tequila brands and their purchases and concluded that a brand's image has a strong impact on purchase loyalty.…”
Section: Introductionmentioning
confidence: 99%